2013
DOI: 10.1111/pce.12204
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines reprogram oxidative and nitrosative status and the proteome of citrus plants exposed to salinity stress

Abstract: The interplay among polyamines (PAs) and reactive oxygen and nitrogen species (RNS and ROS) is emerging as a key issue in plant responses to salinity. To address this question, we analysed the impact of exogenous PAs [putrescine (Put), spermidine (Spd) and spermine (Spm)] on the oxidative and nitrosative status in citrus plants exposed to salinity. PAs partially reversed the NaCl-induced phenotypic and physiological disturbances. The expression of PA biosynthesis (ADC, SAMDC, SPDS and SPMS) and catabolism (DAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
126
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(141 citation statements)
references
References 98 publications
11
126
0
1
Order By: Relevance
“…In citrus plants 271 S-nitrosylated proteins were identified as being polyamineregulated [55]. As Fe-superoxide-dismutase, dehydroascorbate reductase and monodehydroascorbate reductase are also polyamine-induced S-nitrosylation target proteins, NO-modulated S-nitrosylation is also a possible link between polyamines and stress responses [51].…”
Section: Signaling Components Providing Linkage Between Polyamines Anmentioning
confidence: 99%
See 1 more Smart Citation
“…In citrus plants 271 S-nitrosylated proteins were identified as being polyamineregulated [55]. As Fe-superoxide-dismutase, dehydroascorbate reductase and monodehydroascorbate reductase are also polyamine-induced S-nitrosylation target proteins, NO-modulated S-nitrosylation is also a possible link between polyamines and stress responses [51].…”
Section: Signaling Components Providing Linkage Between Polyamines Anmentioning
confidence: 99%
“…As Fe-superoxide-dismutase, dehydroascorbate reductase and monodehydroascorbate reductase are also polyamine-induced S-nitrosylation target proteins, NO-modulated S-nitrosylation is also a possible link between polyamines and stress responses [51]. The mode of action by which polyamines affect S-nitrosylation may differ for individual polyamines [55]. They influence the stress responses of plants through interconversion loops occurring in the polyamine cycle, since H 2 O 2 , as an upstream signaling molecule, also leads to NO production in plants.…”
Section: Signaling Components Providing Linkage Between Polyamines Anmentioning
confidence: 99%
“…Rosales et al (2012) found that PAs can regulate the combination of 14-3-3 proteins with the H + -ATPase, thereby inducing NR activity. Tanou et al (2014) indicated that Spm can increase the relative expression of leNR in citrus under salinity stress. In addition, compared to control, treatment with Spd increased transcript levels of leNR in tomato, but exogenous Put did not alter leNR expression under chilling stress.…”
Section: Nos and Nr Pathways Involved In Spd-induced No Synthesis In mentioning
confidence: 99%
“…Furthermore, some reports have focused on proteomic approaches whereby post-translational modification (PTM) phenomena such as tyrosine nitration, carbonylation, and S-nitrosylation events were also identified in response to chemical priming [56,57]. Interestingly, it was shown that application of H 2 O 2 or application of SNP led to RNS-linked PTMs (i.e., S-nitrosylation) or ROSlinked PTMs (i.e., carbonylation), respectively; this observation provides further support for the interaction between these molecules…”
Section: Promising Chemicals: Assessment Of Common Components Of the mentioning
confidence: 99%